Let's Talk: African Caribbean Women, Mothering Motherhood, and Well-Being - Brown, Geraldine (Frontiers in Sociology, 2020)
In the UK, African Caribbean women’s experience of mothering and motherhood is often studied in isolation from how ‘race’ structures and shapes their everyday reality, health and subjective well-being. The failure to consider how such factors are implicated in the lives of African Caribbean mothers in the UK is absent in debates and policies aimed at addressing concerns associated with ‘gangs’ and ‘urban gun crime' (UGC). Indeed, ‘gangs’ and ‘urban gun crime’ are primarily viewed using a deficit model in which lone motherhood and/ or ‘poor’ mothering within the African Caribbean communities are presented as causal factors. This paper draws on my doctoral research which employed an intersectional analysis informed by an analysis of the meanings and the actions uncovered in accounts shared by men and women who, like me, share a racialised identity and genealogical link to the Caribbean and can be located within or position ourselves within an African Caribbean ‘community’ understood and responded to ‘UGC’. Adopting a critical ethnographical approach, the study created ‘space’ for 'us' as Black women to ‘reason’, to share experiences of womanhood, motherhood and mothering and doing so shed light on dimensions of motherhood and mothering for African Caribbean women that are habitually ignored. In reasoning together, women in my study spoke about the importance of ‘doing mothering and motherhood right,’ this was alongside sharing the stress and anxiety about what they perceived as the dire ramifications of getting things ‘wrong.’ My research captures some valuable insights about Black women’s lives and experiences of mothering and motherhood; their love, commitment and aspirations for their child/ren but it also highlights the emotional labour expended due to the stress and anxiety experienced in the daily strategies employed to prevent a child/ren from being harmed and negatively impacted in their interactions with state institutions. The research confirms the significance of race, racialisation and racism to our lives and experiences of health and subjective well-being and raises critical questions for the dominant and normative view of mothering and/ or motherhood that underpin UK policy and practice.